Sensitivity analysis of the beam optics of a superconducting gantry for proton therapy - Wongso, Shelvia (2018)
A superconducting gantry design is proposed to reduce the size, weight, and complexity of the gantry in the proton therapy facility in Paul Scherrer Institut (PSI), Switzerland. In this thesis, two beam optics programmes, namely TRANSPORT and COSY INFINITY 9.1, have been used to determine the most sensitive magnets in the new gantry beam line with respect to mechanical shift and varying eld strength. The sensitivity analysis is crucial considering the required precision of the pencil beam to hit the tumour at the targeted position within 0.5 mm error with beam size deviation of not more than 0.5 mm. The analysis with both programmes has veri ed that the second normal conducting quadrupole in the beam line is a very sensitive element with respect to horizontal misalignment ( 0.17 mm) while both of the normal conducting quadrupoles are very sensitive with respect to vertical misalignment (0.15 mm). Furthermore, the two normal conducting quadrupoles possess small tolerance of approximately 2.3 T/m with respect to variation in eld strength. It was also found that the phase spaces changed the most when the eld strengths of the superconducting magnets were altered. The tolerance range in each magnet presented in this thesis serves as a gauge for the precision required when designing and mounting the magnets. The values are also important when necessary improvement and corrections to the beam line are considered in order to deliver the desirable beam size at the correct location.